Comparative study of properties of BCZT ceramics prepared from conventional and sol-gel auto combustion powders - Piyaporn Jaimeewong (2018)
© 2016 Taylor & Francis Group, LLC. This work studies properties of Ba0.85Ca0.15Ti0.9Zr0.1O3(BCZT) ceramics prepared from the BCZT powders synthesized by conventional mixed oxide (so called M) and sol-gel auto combustion (so called A) methods. The M and A powders were calcined at 1200 and 900°C, respectively. Different amounts (0, 50 and 100 wt%) of A powder were added into M powder then sintered at 1450°C for 2 h. Grain size and dielectric constant (ϵr) tended to decrease with A powder content. The highest ϵrvalue of 5342 but slimmest was observed in the ceramic with 100 wt% A powder addition.